Short-afferent inhibition and cognitive impairment in Parkinson's disease: A quantitative review and challenges. (6th February 2020) - Martin-Rodriguez, Juan Francisco; Mir, Pablo
Highlights: Short afferent inhibition is a non-invasive marker of cortical cholinergic function. Literature reports moderate to severe alterations in SAI associated to PD. Disease duration and dopaminergic medication modulate SAI in patients with PD. Diminished SAI is associated with worse cognitive functions in PD. Abstract: Traditionally, Parkinson's disease (PD) has been considered a single neurotransmitter (dopaminergic) disease. However, research over the past 20 years has shed light on the involvement of multiple neurotransmission systems, in particular, the cholinergic system. Research has mainly focused on the role of this system in the pathophysiology of PD and its implications in the development of motor and non-motor disorders. Short-latency sensory afferent inhibition (SAI), investigates sensori-motor integration, and has emerged as a putative neurophysiological marker of cholinergic function in the human brain. In this quantitative review, a moderate-to-severe reduction in SAI was observed in PD patients. Furthermore, through moderator analysis, the impairment of SAI was shown to be associated with disease duration and therapeutic state. Patients under dopaminergic agents ("on" state) displayed worse SAI than those after dopaminergic agent withdrawal ("off"). We further assess the potential value of SAI as a marker of cognitive impairment in PD, and its association with four specific cognitive domains. This analysis revealed that patients with cognitive impairment displayed significantly lower levels of SAI than those without cognitive impairment. To conclude, a set of challenges to be addressed before SAI can be validated as a useful clinical tool in PD are presented.